Design and development of a polymer patch clamping device - Wilson, Sandra (Cranfield University, 2010)
Patch clamping is considered the gold standard in measuring the bioelectrical activity of a cell. It is used to detect and measure ion transport through ion channels located throughout a cell membrane. Ion movement is crucial to cell viability and cell-to-cell communication. Pharmaceutical companies increasingly target ion channels because of their significance in disease and to help design better targeted drugs. However, the traditional method of patch clamping is cumbersome and is being replaced by planar high throughput screening (HTS) systems. These systems are reaching their limits due to materials and cost of processing; cell handling methods and small varieties of applicable cell types are also issues to be addressed. In this work, the core components of a new kind of planar patch clamping device have been designed and developed, after analysis of currently available HTS systems. This design approaches patch clamping using polymers to overcome some of the limitations in current systems, specifically cell handling and positioning, by using a simple modification technique to provide distinct attractive areas for cell binding. This uniquely allows the culture of both single cells and cell networks to increase the range of cell types that can be measured and circumvents challenges from using suction to pull cells onto measurement holes. The components of the design are a 10 x 10 array of small holes drilled in a polymer then aligned modifications for precise cell placement are added and a planar electrode array for individual addressing of each cell. A study of methods to produce a leak-tight seal required between microfluidic chambers was done. Cell adhesion parameters for the modification techniques were established. The principle viability of this approach was confirmed using the modification technique to culture cells over holes and measure their resistance using a rig developed for this work.
Keywords: bioMEMs; patch clamping; microhole drilling; polymer surface modification